2006
DOI: 10.1590/s0100-879x2006001200005
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic inventory of myocardial proteins from patients with chronic Chagas' cardiomyopathy

Abstract: Chronic Chagas' disease cardiomyopathy (CCC) is an often fatal outcome of Trypanosoma cruzi infection, with a poorer prognosis than other cardiomyopathies. CCC is refractory to heart failure treatments, and is the major indication of heart transplantation in Latin America. A diffuse myocarditis, plus intense myocardial hypertrophy, damage and fibrosis, in the presence of very few T. cruzi forms, are the histopathological hallmarks of CCC. To gain a better understanding of the pathophysiology of CCC, we analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…Proteomic profiling of myocardium from CCC patients revealed that 27 % of identified proteins belong to energy metabolism pathways [27]. Using gene expression profiling, our group found differential expression of a significant number of genes involved in oxidative phosphorylation and lipid catabolism in myocardial samples from CCC patients, but not in samples from patients with dilated cardiomyopathy, when compared to samples from subjects without cardiomyopathy [15].…”
Section: Introductionmentioning
confidence: 88%
“…Proteomic profiling of myocardium from CCC patients revealed that 27 % of identified proteins belong to energy metabolism pathways [27]. Using gene expression profiling, our group found differential expression of a significant number of genes involved in oxidative phosphorylation and lipid catabolism in myocardial samples from CCC patients, but not in samples from patients with dilated cardiomyopathy, when compared to samples from subjects without cardiomyopathy [15].…”
Section: Introductionmentioning
confidence: 88%
“…Gene expression profiling also disclosed that lipid metabolism and mitochondrial oxidative phosphorylation genes were selectively modulated in CCC myocardial tissue, suggesting a specific energy imbalance. Using proteomic analysis (bidimensional electrophoresis and MALDI-TOF mass spectrometry), our group has established a proteomic inventory of >100 distinct myocardial proteins in CCC myocardial tissue [46]. Preliminary data from differential protein expression analysis in the myocardium of CCC, DCM, and ischemic cardiomyopathy (IC) patients as compared to control heart donor myocardial samples allowed the identification of prominently altered pathways, including cardiac remodeling and depressed energy metabolism.…”
Section: Immunological Dynamics During the Acute And Chronic Phasementioning
confidence: 99%
“…Our group has recently described an inventory of myocardial proteins from patients with severe CCC. This has allowed us to identify proteins with high and low abundance in the tissue, including proteins with structural, metabolic, stress, apoptosis and immune response functions (TEIXEIRA et al, 2006). It would be interesting to investigate whether the expression of cardiac proteins differs between severe CCC patients and mild CCC or IND subjects.…”
Section: Immunopathogenesis Of Chagas Disease Cardiomyopathymentioning
confidence: 99%